E-Module Bahasa Pemrograman Java Berbasis Exe-Learning - Rahmat Musfikar; Ichsanul Akbar; Sarini Vita Dewi; Aulia Syarif Aziz (LPPM Universitas Dinamika Bangsa, 2023)
Learning informatics is often considered a difficult subject by junior high school (SMP) students, especially in the introduction of algorithms and programming languages. There are many variables that cause problems that teachers often face when teaching informatics. One of them is the unavailability of learning media. Therefore, research was conducted to discuss learning media for the Java programming language using Exe-Learning. The purpose of this study is to produce learning media that contains material on the introduction of algorithms and the introduction of the Java programming language. In designing and building this learning media using the ADDIE method which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. This research produced learning media in the form of Java Programming Language E-Modules. This learning media has been tested and validated by media experts and material experts with the validation results of this learning media expert with a percentage of 90% and material experts with a percentage value of 95.38%, indicating that this media is very feasible to use as a learning resource in subjects informatics, especially on material algorithms and programming languages